1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00052.x
|View full text |Cite
|
Sign up to set email alerts
|

SP‐22 is a Thioredoxin‐Dependent Peroxide Reductase in Mitochondria

Abstract: SP-22 is a mitochondrial antioxidant protein in bovine adrenal cortex. The protein is homologous to thioredoxin peroxidase and other antioxidant proteins. It protects radical-sensitive enzymes from oxidative damage by a radical-generating system (Fe'+/dithiothreitol ) in the presence of a small amount of serum. In this study we purified a second mitochondrial protein with M , 11 777, which cooperates with SP-22 to protect glutamine synthetase and other proteins from Fe2+/dithiothreitol-mediated damage. Without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 44 publications
4
91
0
1
Order By: Relevance
“…Peroxiredoxins are in different subcellular compartments. While Prx III is localized to mitochondria [12,22,54,55], Prx I and Prx II are found in the cytoplasm [15,23,32,43]. Furthermore Prx I is thought to be translocated into the nucleus by association with other proteins such as tyrosine kinase c-Abl, though given its small size it could enter passively [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxiredoxins are in different subcellular compartments. While Prx III is localized to mitochondria [12,22,54,55], Prx I and Prx II are found in the cytoplasm [15,23,32,43]. Furthermore Prx I is thought to be translocated into the nucleus by association with other proteins such as tyrosine kinase c-Abl, though given its small size it could enter passively [34].…”
Section: Discussionmentioning
confidence: 99%
“…19] and catalyse reduction of both hydrogen peroxide and alkyl peroxides to water or to the corresponding alcohol using thioredoxin (Tx) as their physiological hydrogen donor [20,21,22,23,24]. Additionally it has been shown that the bacterial peroxiredoxin AhpC (alkylhydroperoxide reductase subunit C) is able to protect against nitrogen radicals [25].…”
mentioning
confidence: 99%
“…Two mitochondrial Prdx isoforms have been identified so far. Prdx3, originally cloned from murine erythroleukemia cells (30), is exclusively detected in mitochondria (31). Prdx3 expression can be induced in response to oxidant treatments, and antisensemediated inhibition of Prdx3 expression was shown to sensitize bovine aortic endothelial cells to oxidative challenges (32).…”
mentioning
confidence: 99%
“…PRDX1 and 2, also referred as natural killer enhancing factors (NKEF-A, NKEF-B), are localized in the cytosol [6,7], whereas the other members of the 2-Cys PRDX subclass are widely distributed with PRDX3 in mitochondria [8], PRDX4 in endoplasmatic reticulum and extracellular space [9] and PRDX5 in cytosol, mitochondria and peroxisomes [10]. In contrast, PRDX6 is restricted to cytosol [11], and the catalytic efficiency of all PRDXs is less than that of catalase or glutathione peroxidases by one or three orders of magnitude [12].…”
Section: Introductionmentioning
confidence: 99%